Perlindungan Hukum Terhadap Konsumen Atas Perbedaan Tarif Paket Internet Yang Ditawarkan oleh Telkomsel - Satrianingtyas, Auliya Ayu (LPPM Universitas Ekasakti Padang, 2024)
In the era of globalization marked by advancements in communication technology, Indonesia has seen a significant increase in smartphone usage. Smartphones, now almost equivalent to computers in capabilities and functions, play a key role in providing access to the internet and applications that enrich the digital lifestyle of their users. This research focuses on PT. Telkomsel, a leading cellular operator in Indonesia, which has adopted various technological innovations including prepaid GSM services, 3G, and 4G, as well as preparing for 5G. Telkomsel not only plays a role in connecting millions of users through a broad network but also in promoting digital access via the MyTelkomsel app. However, this study also critiques the practice of Telkomsel's differential tariff setting based on zones and consumer profiles, which poses potential discrimination. Referring to the Consumer Protection Law, this study explores the implications of such practices on consumer rights and offers recommendations for fairer and more transparent consumer protection in the telecommunications industry. This research provides vital insights into the balance between technological innovation and consumer ethics in the context of modern business.